(untitled) (Pravaha, 2024)
Purpose of this study is to measure the impact of earnings per share, book value per share, dividend per share, total assets, and non-performing loan on market value per share per share of commercial banks in Nepal. Descriptive, correlational, and casual comparative research design used in this study. This study examined data from secondary sources. Information was gathered from the corresponding bank’s annual audit report. This study investigated data from fiscal years 2012–13–2022–2023 from 26 and 19 commercial banks before and after merger. Rastriya Baanijya Bank, which is entirely owned by the government, is not included in this study’s analysis of all commercial banks. The mean, maximum, minimum, standard deviation, and coefficient of variation are descriptive statistical methods that were employed in this investigation. Inferential statistical procedures such as multiple regression analysis and correlation analysis were also employed in this investigation. Highest dispersion in dividend per share, non-performing loan, book value per share, earnings per share, market value per share, and total assets respectively based on coefficient of variation. There is direct association of book value per share with earnings per share, dividend per share, and total assets but negative association between market value per share and non-performing loan. Insignificant association between market value per share and book value per share. There is positive impact of earnings per share, dividend per share, and total assets on market value per share. Out of these, total assets highest influenced on market value per share. Non- performing loan negative impact on market value per share but there is insignificant impact of book value per share on market value per share of commercial banks in Nepal.